1992
DOI: 10.1002/cjce.5450700125
|View full text |Cite
|
Sign up to set email alerts
|

Surface tensions and contact angles due to lignin sulphonates in the system: Liquid sulphur, aqueous zinc sulphate and zinc sulphide

Abstract: Surface tension and contact angle measurements were made in the liquid sulphur-aqueous zinc sulphate-zinc sulphide system at superatmospheric pressures, and showed that, in the absence of surfactants, the liquid sulphur-aqueous solution interfacial tension was 54.0 & 1 .O mN/m, falling to 27.0-30.0 mN/m when 0.3 g/L or more of lignin sulphonate was added to the solution. At the same time, the contact angle between liquid sulphur and the same solution increased from 80 5 5" to 148 & 5 " . As a result, the work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
1
1
2
Order By: Relevance
“…With the lignin added, the silver extraction percentage increases to 94.5 pct, but the zinc extraction percentage remains constant at about 6 pct. These results are inconsistent with those of Owusu, [21,28] who showed that the extraction percentage of zinc in pressure leaching increased from 50 pct to 93.6 pct (0.1 g/L lignin) or 99.8 pct (0.1 g/L orthophenylene diamine). The reason for the high silver extraction percentage in our experiments without adding surfactants is that some organic amines were used during the flotation process and ultimately remained in the silver flotation concentrates.…”
Section: F Effect Of Lignin Additioncontrasting
confidence: 78%
“…With the lignin added, the silver extraction percentage increases to 94.5 pct, but the zinc extraction percentage remains constant at about 6 pct. These results are inconsistent with those of Owusu, [21,28] who showed that the extraction percentage of zinc in pressure leaching increased from 50 pct to 93.6 pct (0.1 g/L lignin) or 99.8 pct (0.1 g/L orthophenylene diamine). The reason for the high silver extraction percentage in our experiments without adding surfactants is that some organic amines were used during the flotation process and ultimately remained in the silver flotation concentrates.…”
Section: F Effect Of Lignin Additioncontrasting
confidence: 78%
“…Establishing the cause of the insufficient effectiveness of LS and the development of new highly effective surfactants and formulations of multicomponent surfactant compositions are constrained by the lack of data on interfacial phenomena, namely, the processes of adsorption, wetting, and dispersion of minerals with the participation of surfactants under conditions simulating the autoclave leaching of ores. It should be emphasized that targeted studies of surface phenomena at the mineral–elemental sulfur–surfactant boundary, carried out by Naboychenko, Goryachkin, Shneyerson, Owusu, Dreisinger, and Naftal , have certainly significantly advanced our understanding of the mechanisms of implementation of the surface effect of surfactants. Meanwhile, a number of issues remain which require practical verification and theoretical substantiation, in particular, the effect of the ionic composition of the liquid phase on the processes of wetting and adsorption of minerals and elemental sulfur has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…За прошедшие десятилетия был накоплен большой опыт реализации АОВ цинковых концентратов [3,6], получены данные о кинетике процесса, влиянии состава концентратов [7][8][9][10][11][12][13][14][15][16][17][18][19] и добавок на эффективность выщелачивания [20,21].…”
Section: Introductionunclassified